Communicating for results a guide for business and the professions - Hamilton, Cheryl (Australia Wadsworth Cengage Learning, 2014)
"This best-selling text will show you the basic concepts and techniques you need to successfully communicate in today's business world, regardless of your current level of business experience. Covering every aspect of the communication process, Communicating For Results: A Guide for Business and the Professions, tenth edition, will give you a competitive edge in any business situation -- from the initial interview to making skilled presentations (complete with professional visual aids) to assuming a leadership role. In addition, you'll find online video clips of common professional scenarios paired with the concepts from the text give you a realistic glimpse into the business world. Communicating For Results: A Guide for Business and the Professions, tenth edition, is your opportunity to see how theory translates into practical action -- and how that knowledge will help you improve your chance of career success!"--from the publisher.
Communication process: an introduction -- Communication in the workplace -- Conflict, culture, and relationships -- Effective listening -- Nonverbal communication -- Overcoming obstacles to communication in the electronic age -- Basic infromation for all types of interviews -- The employment interview -- Small-group communication and problem solving -- Participation and leadership in teams -- Informative presentations: plan, research, organize, and deliver -- Verbal and visual supporting materials -- Persuasive presentations: individual or team -- Polishing your written communication.
Previous edition: 2011.
Includes bibliographical references (pages 467-496) and indexes.
Keywords: Communication in management